Development of student’s worksheet based Bas-basan traditional game in rectangular and triangle - Ubaidillah, Moh Fernando Muiz; Khotimah, Rita Pramujiyanti (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
Local culture is rarely known to today's children. Learning innovations related to culture are important to develop in schools. The aim of this research is to develop student worksheets on quadrilaterals and triangles based on the traditional game Bas-basan that are valid and practical. This research uses the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development research model. Data collection methods through interviews and questionnaires. The interview results were analyzed descriptively, then the results of the validity and practicality assessments were analyzed quantitatively and qualitatively. The findings showed that the validity of the student worksheet developed met the valid criteria with a score of 3.11. Then, the results of the practicality assessment showed that the worksheet developed met the practicality criteria with a score of 3.085. Thus, it can be concluded that ethnomathematics-based student worksheets with traditional bas-basan games are suitable for use in learning quadrilaterals and triangles.